Оцінка впливу втрат тиску в системі збору газу на обсяги його видобутку - Братах, Михайло Іванович (НТУ "ХПІ", 2012)
Theoretical justification of flowing pressure reserve search in wells on the closing stage of development are presented in the paper by example of Svidnitsky zone of Svidnitsky field and the ways of its realization in practice of running surface facility with evaluation of indicative volume of additional produced gas.
Keywords: енергозбереження; видобуток газу; газотранспортна система; газопровід; транспортування газу; родовища природного газу України; свердловина; система збору газу